2019
DOI: 10.1364/josaa.36.001015
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of the ocular surface temperature dynamics in glaucoma subjects using long-wave infrared thermal imaging

Abstract: We evaluated the dynamics of ocular surface temperature using thermal imaging in 21 glaucoma subjects and 19 healthy subjects. On opening of the eye, subjects with glaucoma showed significantly cooler temperatures in the central cornea compared to the control group. The upper eyelid was also significantly cooler just before the eye opened. Immediately after opening the eye, the dynamic of temperature change was different in the two groups. In subjects with glaucoma, the eyes cooled significantly faster, with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
1
10
0
1
Order By: Relevance
“…4,5 The observed differences in OST might have also resulted from vascular changes: surface temperature directly correlate with tissue blood-flow. Since IOP is has been shown to inversely correlate with ocular blood flow, the OST of glaucoma eyes is expected to be lower than observed in healthy eyes, similar to the findings described by Garcia-Porta et al 21 However, in our cohort due to proper management, the mean IOP of the glaucomatous eyes was similar to that measured in healthy eyes. Therefore, the effects of changes in ocular blood supply on thermal dynamics of the ocular surface were obscured by that of the low-grade inflammation.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…4,5 The observed differences in OST might have also resulted from vascular changes: surface temperature directly correlate with tissue blood-flow. Since IOP is has been shown to inversely correlate with ocular blood flow, the OST of glaucoma eyes is expected to be lower than observed in healthy eyes, similar to the findings described by Garcia-Porta et al 21 However, in our cohort due to proper management, the mean IOP of the glaucomatous eyes was similar to that measured in healthy eyes. Therefore, the effects of changes in ocular blood supply on thermal dynamics of the ocular surface were obscured by that of the low-grade inflammation.…”
Section: Discussionsupporting
confidence: 89%
“…11,12,15 Currently, only a few small studies have examined the use of OST measurements in the setting of glaucoma. 13,21 Based on previous reports we hypothesized that the OST can be affected by the inflammatory processes involved in the pathophysiology of glaucoma. The purpose of this study was to test this hypothesis by comparing the thermographic measurements of OST in the eyes of healthy subjects with those of patients with primary open angle glaucoma (POAG) or pseudo exfoliation glaucoma (PXFG), and determine whether these measurements can be used as a disease biomarker.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the applicability of results from the current study to different patient groups with ocular surface abnormalities, dry eye, ocular inflammation, or other ocular diseases, as well as individuals wearing contact lenses, must be clarified. 15 , 23 , 24 , 27 31 Finally, the current study did not control the timing of the photographs after blinking and did not compare different shapes and sizes of central corneal areas for temperature calculations. 30 The influences of these parameters on the stability of temperature measurement are unknown.…”
Section: Discussionmentioning
confidence: 95%
“…No significant interocular difference in OST has been reported in animals and humans. [30,33,41,42,54,55]. Morgan and colleagues [34] found that 95 percent of the normal population have an interocular temperature difference of 0.60 degrees or less.…”
Section: Temperature Of and Heat Flux From The External Ocular Surfacementioning
confidence: 99%